Assessment of Sustainable Development of the Residential Construction Sector in the Context of Sustainable City Development in Poland - Sitek, Marcin (European Journal of Sustainable Development, 2018)
The issue of quality of life in large agglomerations has become more and more important for many years. The challenges faced by the real estate market relate to its planned further development taking into account all dimensions of sustainable development. The aim of the work is to assess the state of sustainable development of the residential construction sector in Poland. The work assumes that sustainable development of construction is one of the factors determining sustainable development of cities. The research was based on statistical data describing housing resource in Poland and on analyses and reports published by the Central Statistical Office, NBP, Responsible Business Forum and Agenda for Sustainable Development 2030. The goals of Agenda 2030 were discussed with particular emphasis on stability and sustainability of the real estate market. The value of the urbanization index for large agglomerations in Poland confirmed the very positive effects of the sustainable development of the real estate market. The paper attempts to determine the relationship between the economic value of the housing sector and the consumption of environmental resources, which may lead to the establishment of an indicator that is a new tool for assessing sustainable development. The analysis carried out in the work thus confirmed the legitimacy of the thesis put in place, leading to the realization of the aim of the work Keywords: Agenda 2030, urbanization, construction sector, real estate market, sustainable development